Creating Educational Networking Opportunities with Scoop.it. (July 2014) - Antonio, Amy; Tuffley, David
The adoption of social media technologies by higher education institutions reflects a significant change in learning paradigms. The traditional classroom model in which instructors were the sole source of information and knowledge is being replaced by a social constructivist model that allows learners to work together to share and create content. This study explores the potential of the digital curation platform Scoop.it as a networking tool among a group of first year Information Communication Technology (ICT) students. It will be shown that Scoop.it is a useful platform for the creation and sharing of information resources with other students and the wider community. Scoop.it facilitates the creation of networks for information sharing and knowledge building, which will be referred to as educational networking, but was less successful as a platform for forming social connections.